Improving the Students’ Motivation in Learning English through Google Meet during the Online Learning - Rizal Wahid Permana Putra (English Learning Innovation (englie), 2021)
The increase number of Covid-19 outbreak has profoundly changed our education system. This condition has led the teachers to alter the face-to-face learning into online learning. Online learning emphasizes on the internet-based courses synchronously and asynchronously. Besides its technical problems, conducting online learning was said to be monotonous since the teachers preferred doing online tasking to providing effective learning experience. Further, this condition led to low students’ motivation in learning English. In other words, the students might be in boredom to participate and engage in the teaching- learning process owing to the monotonous learning. Most students were said to be late or even reluctant to complete the assignments. Therefore, the researcher conducted the Classroom Action Research dealing with the use of Google meet to improve the students’ motivation in learning English during the online learning. The research subject was the 7th grade students of SMP Negeri Satu Atap Jarit. The research was conducted in two cycles. In cycle I, it showed that there was an increase of students’ motivation in learning English. The increase of students’ motivation was 61, 8%. Meanwhile, in cycle II, the researcher found that the Google meet significantly improved the students’ motivation in learning English. The increase of students’ motivation was 79, 4%. The result showed that the students actively participate and engage in the teaching-learning process. The students were very enthusiastic to respond and answer the some questions, and share their ideas related to the topic of the meeting. In addition, the increase of students’ motivation influence the students to compose sentences correctly related to the given assignments. Based on the result of data analysis, the researcher drew a conclusion that the use of Google meet significantly improved the students’ motivation in learning English during the online learning.Keywords: Google meet, Learning English, Students’ Motivation